Say No to blue publishing: Yogyakartan indie publishers' counter hegemony and resistance strategies against major publishers. - Alkatiri, Zeffry; Aviandy, Mochamad; Gani, Fuad; Primadesi, Yona (Continuum: Journal of Media & Cultural Studies, 2026)
Major publishing companies, often called 'blue publishers,' dominate Indonesia's publishing ecosystem, including Yogyakarta. This article examines the resistance strategies of Yogyakartan indie publishers from 2000 to 2022. The 1998 reformation marked the turning point of such resistance, which gained momentum between 2015 and 2020 with the Kampung Buku Jogja Festival, continuing until the Covid-19 pandemic (2020–2022). Indie publishers disrupted the hegemonic distribution chain by adopting social media, e-commerce and e-business, carving out alternative networks outside mainstream control. The study documents and analyzes these strategies through selected references, interviews and focus group discussions with publishing stakeholders in Yogyakarta, conducted over 4 months (May to August 2022). Using a qualitative-descriptive method and a cultural studies approach, the research explores the factors, reasons, forms and strategies behind indie publishers' resistance. Findings reveal that Yogyakartan indie publishing has successfully occupied spaces neglected by major publishers, creating a dynamic ecosystem of cultural resistance within Indonesia's book industry.